1998
DOI: 10.1023/a:1011986028529
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The overall mechanisms of the N-B transition may be similar for all the albumins, but its impact is considerably different among the species in terms of both structural characteristics and ligand binding properties. Furthermore, the transitions appear to be multi-step transitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…Then, different volumes of the heme-HSA solution (in the absence and presence of the chaotropic agent) were mixed to obtain the desired GnCl concentration at a fixed heme-HSA concentration. GnCl-induced HSA unfolding is fully reversible under the experimental conditions reported in the present study [25][26][27][28][29][30][31][32]. Samples were incubated for 1 h before measurements.…”
Section: Methodsmentioning
confidence: 64%
See 1 more Smart Citation
“…Then, different volumes of the heme-HSA solution (in the absence and presence of the chaotropic agent) were mixed to obtain the desired GnCl concentration at a fixed heme-HSA concentration. GnCl-induced HSA unfolding is fully reversible under the experimental conditions reported in the present study [25][26][27][28][29][30][31][32]. Samples were incubated for 1 h before measurements.…”
Section: Methodsmentioning
confidence: 64%
“…The multidomain structural organization makes HSA a model system to investigate how interdomain interactions could affect the folding/unfolding process [25][26][27][28][29][30][31][32]. With use of different experimental techniques to follow thermal or chaotropic denaturation of HSA, it has been observed that the HSA N state unfolds in two sequential steps, domain II unfolding before domain I (i.e., the heme binding domain) [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In studies with human plasma and ovine serum [38] the eluates from these supports, as well as those from others derivatised with a closely related ligand [37,42], contained significantly less albumin. Comparative studies of differences between hydrophobic drug binding sites [43], chemical and thermal stability [44], and thermal transitions [45] of serum albumins from five mammals, showed significant differences between those from rabbit and human. In light of this, it is conceivable that rabbit albumin could bind more strongly than human albumin to MabSorbents A1P and A2P.…”
Section: Ig Purificationmentioning
confidence: 98%
“…Acyclovir can bind to some sites of HSA by different affinities, which is supported by some crystallographic data [31][32][33]. The structure of domain IA is slightly different from that of the other two domains in the helix of amino acid peptide.…”
Section: Resultsmentioning
confidence: 63%